2005
DOI: 10.1002/ange.200501632
|View full text |Cite
|
Sign up to set email alerts
|

The Aromaticity of the Stannole Dianion

Abstract: In the last decade, much attention has been focused on the anions and dianions of siloles [1] and germoles, [1f, 2] which are heavier congeners of the cyclopentadienyl anion.[3] The degree of aromaticity of silolyl anions depends on the substituent, [1b,f] while the germolyl anions do not show aromaticity because the negative charge is localized on the germanium atom. [1f, 2a,2c] In contrast, the negative charges in the dianions of siloles and germoles are significantly delocalized in the C 4 M (M = Si, Ge)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 39 publications
1
16
0
3
Order By: Relevance
“…In the 7 Li NMR spectrum, an upfield resonance was observed at d = À7.4 ppm, which suggested that the anionic moiety of 5 should be highly aromatic. [9] The carbon atom at the 9-position of some fluorenyllithiums was reported to resonate at about d = 80 ppm. [10] Likewise, in the 13 C NMR spectrum, a 13 C signal at d = 80.47 ppm can be assigned to a carbon atom at the 1-position in the anionic moiety of 5.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the 7 Li NMR spectrum, an upfield resonance was observed at d = À7.4 ppm, which suggested that the anionic moiety of 5 should be highly aromatic. [9] The carbon atom at the 9-position of some fluorenyllithiums was reported to resonate at about d = 80 ppm. [10] Likewise, in the 13 C NMR spectrum, a 13 C signal at d = 80.47 ppm can be assigned to a carbon atom at the 1-position in the anionic moiety of 5.…”
Section: Resultsmentioning
confidence: 98%
“…The intensity data were collected at À170 8C on a Bruker SMART APEX equipped with a CCD area detector with graphite-monochromated Mo Ka radiation (l = 0.71073 ) and graphite monochromater. Formula = C 55 H 93 LiO 9 Reaction of dibenzopentalene 3 with bromine: Bromine (0.22 mL, 4.27 mmol) was added to an ether (10 mL) solution of dibenzopentalene 3 (108.7 mg, 0.21 mmol) at room temperature and the resulting mixture was stirred for 6 h. After addition of saturated aqueous sodium sulfite to the reaction mixture, the organic layer was extracted with ether, dried over anhydrous magnesium sulfate, and concentrated to give a crude product (173.9 mg). The residue was chromatographed on silica gel (hexane) to afford 5,10-dibromodibenzoA C H T U N G T R E N N U N G [a,e]pentalene (8) (54.1 mg, 71 %).…”
Section: Reduction Of Dibenzopentalene 3 With Lithium (Excess)mentioning
confidence: 99%
“…[1,2] For the last decade, much attention has been focused on the investigation of whether aromaticity is maintained or changed by the introduction of heavier Group 14 atoms into p-frameworks. [3,4] Very recently, we have succeeded in the synthesis of dilithioplumbole, which has considerable aromatic character, thus clarifying that incorporating a lead atom into the carbon p-framework does not disrupt its aromaticity.…”
Section: Introductionmentioning
confidence: 98%
“…[2] In particular, much effort has been directed toward the development of a chiral catalyst for epoxidation because of the high utility of optically active epoxides as versatile chiral building blocks. [3,4] However, a general and highly enantioselective epoxidation of unfunctionalized olefins with hydrogen peroxide has not been developed.Recently, we developed a chiral di-m-oxo titanium-salalen (salalen [5,6] : hybrid salan/salen tetradentate (ONNO)-type ligand; salan: N,N,-bis(o-hydroxybenzyl)-1,2-diaminoethane, salen: N,N-bis(salicylidene)ethylenediamine) complex that was able to catalyze the epoxidation of unfunctionalized olefins using aqueous hydrogen peroxide with high enantioselectivity and a high turnover number of the catalyst. [7] The robustness and the unique catalysis of the titanium-salalen complex are in marked contrast with the ineffectiveness of the corresponding di-m-oxo titanium-salen complex as an epoxidation catalyst.…”
mentioning
confidence: 99%